DEMOCRATIC VALUES OF THE UKRAINIAN PEOPLE IN THE CONTEXT OF PHILOSOPHICALAND LEGAL ANALYSIS OF THE THIRD LITHUANIAN STATUTE OF 1588 - ЧЕРНЕЦЬКА, Тетяна (Київський національний університет імені Тараса Шевченка, 2026)
B a c k g r o u n d . The article examines the democratic values of the Ukrainian people in the context of a philosophical and legal analysis of the provisions of the Third Lithuanian Statute of 1588 (hereinafter referred to as the Lithuanian Statute). Given that contemporary geopolitical transformations necessitate research into national identity, the analysis of historical legal monuments becomes particularly relevant. The latter serve as a link between the present and the events of the past, promoting awareness of the fundamental values that shape national identity. M e t h o d s . The research results were achieved using historical-legal, philosophical-legal, comparative-legal, dialectical, and systematic methods, which ensured a comprehensive approach to the analysis of the democratic values of the Ukrainian people embodied in the content of the norms of the Lithuanian Statute. R e s u l t s . An analysis of the arguments in favour of the Lithuanian Statute belonging to the Ukrainian legal tradition has been carried out. Particular attention has been paid to the study of the axiological and essential dimensions of fundamental democratic concepts formalized in the Lithuanian Statute. A comparison of foreign and domestic scientific developments with the key provisions of the Lithuanian Statute contributed, inter alia, to proving the epoch-making and exceptional nature of this legal monument as an integral part of Ukrainian, and therefore European, legal heritage. C o n c l u s i o n s . The Lithuanian Statute is reasonably considered to be a monument of Ukrainian legal creativity. Particular attention is paid to the study of the axiological and essential dimensions of fundamental democratic concepts formalized in the Lithuanian Statute: “freedom,” “will,” and “liberty.” A comparative legal analysis of the document's provisions with foreign and domestic scientific developments has helped to confirm the progressive and far-sighted nature of the Ukrainian legal heritage as one of the key elements of European legal heritage. It has been proven that the Lithuanian Statute is an autochthonous legal monument of the Ukrainian people, which explicitly attests to the continuity of the legal tradition, imbued with the democratic values of will, freedom, human rights, legality, and equality before the law. In accordance with the content of the legal tradition, a semantic analysis of the concepts of “will,” “freedom,” and “liberty” was carried out in correlation with the concepts of Ukrainian legal heritage and national consciousness. Given the presence of philosophical and legal declarations articulated in the preamble to the legal document, a hypothesis is put forward about the dominance of the idea of natural law guiding lawmakers, as evidenced by the human-centered orientation of the content of the Lithuanian Statute. The importance of the principle of legal awareness is emphasized, which is a fundamental guarantee of the possibility of realizing and, accordingly, protecting one's rights and freedoms by representatives of the whole society. The principle of its territorial application is emphasized, which contributed to the influence of this legal monument on the formation of the legal consciousness of the peoples whose lands were part of the Polish-Lithuanian Commonwealth. This gives grounds to assert the influence of the Ukrainian legal tradition on the legal traditions of these peoples, and to refer to the Lithuanian Statute as a common achievement of European legal heritage.

В с т у п . Досліджено демократичні цінності українського народу в розрізі філософсько-правового аналізу положень Третього Литовського статуту 1588 р. (далі Литовський статут). З огляду на те, що сучасні геополітичні трансформації зумовлюють необхідність дослідження своєї національної ідентичності, особливої актуальності набуває аналіз історичних правових пам'яток. Останні виконують роль сполучної ланки між сучасністю та подіями минулого, сприяючи обізнаності у фундаментальних цінностях, що формують національну ідентичність. М е т о д и . Результатів дослідження досягнуто з використанням історико-правового, філософсько-правового, порівняльно-правового, діалектичного та системного методів, які забезпечили комплексний підхід до аналізу демократичних цінностей українського народу, втілених у змісті норм Литовського статуту. Р е з у л ь т а т и . Здійснено аналіз аргументації на користь належності Литовського статуту до пам'ятки української правової творчості. Особливу увагу приділено дослідженню аксіологічного і сутнісного виміру фундаментальних демократичних понять, формалізованих у Литовському статуті. Зіставлення іноземних і вітчизняних наукових напрацювань разом із ключовими положеннями Литовського статуту сприяло, inter alia, доведенню епохальності та винятковості зазначеної правової пам'ятки як складової частини української, а отже, і європейської правової спадщини. В и с н о в к и . Аргументовано належність Литовського статуту до пам'ятки української правової творчості. Особливу увагу приділено дослідженню аксіологічного і сутнісного виміру фундаментальних демократичних понять, формалізованих у Литовському статуті: "вольність", "воля", "свобода". Порівняльно-правовий аналіз положень документа з іноземними й вітчизняними науковими напрацюваннями сприяв засвідченню прогресивності та далекоглядності характеру української правової спадщини як однієї із ключових елементів європейської правової спадщини. Доведено, що Литовський статут є автохтонною правовою пам'яткою українського народу, що експліцитно засвідчує тяглість правової традиції, змістовно пронизаної демократичними цінностями волі, свободи, прав людини, законності та рівності перед законом. Відповідно до змісту правової традиції здійснено семантичний аналіз понять "воля", "вольність" і "свобода" у кореляції з поняттями української правової спадщини й національної свідомості. З огляду на присутність філософсько-правових декларацій, артикульованих у преамбулі правової пам'ятки, висловлено гіпотезу про домінування керівної для нормотворців ідеї природного права, про що свідчить людиноцентристське спрямування змісту Литовського статуту. Підкреслено вагомість принципу правової обізнаності, що є фундаментальною гарантією можливості реалізації та, відповідно, захисту своїх прав і свобод представниками всього суспільства. Наголошено на принципі територіальної його дії, що сприяло впливу цієї правової пам'ятки на формування правової свідомості народів, землі яких входили до складу Речі Посполитої. Це дає підстави стверджувати про вплив української правової традиції на правові традиції цих народів, а про Литовський статут – як про спільний набуток європейської правової спадщини.
ДЕМОКРАТИЧНІ ЦІННОСТІ УКРАЇНСЬКОГО НАРОДУ У СВІТЛІФІЛОСОФСЬКО-ПРАВОВОГО АНАЛІЗУ ТРЕТЬОГО ЛИТОВСЬКОГО СТАТУТУ 1588 РОКУ
Keywords: democratic values; human-centeredness; natural rights; Lithuanian Statute; legal identity; legal culture; Ukrainian legal tradition; демократичні цінності; людиноцентризм; природні права; Литовський статут; правова ідентичність; правова культура; українська правова традиція